(untitled) (Fiep Bulletin - online, 2011)
The school is an institution that serves to socialize the individual and is the meeting point between students and society. There are different perceptions between school and society, but that is more dirertamente and present in our lives is the concept that the school has a relative autonomy, where we can enter the school from within the society. Educators who care about the education of society create media that reach all social strata, including the popular class, to try to ensure you a quality education. Popular education in this society we live in, is seen as unimportant, valueless, taken as a challenge. One problem faced by the very popular class is the violence outside the school that eventually influenced the violence inside the school. The violence is in the everyday lives of these people who have to elaborate means to live with it, because episodes of violence are reported with significant intensity, both from the information provided by students and by educators. The biggest problems are the quarrels, assaults, threats and drug use. For educators the larger problems are verbal abuse, vandalism, threats and intimidation. Professionals in public more often to watch these episodes than their peers in private schools. This phenomenon of violence in schools is directly linked to that crime affects young people in urban areas and are in poorer communities. Solve this complex problem is not an easy task, but we should try to change this situation to try to block the growth of these problems presented and give a new way to stay in school that are always on the verge of exclusion.